Analytical reversed‐phase high‐performance liquid chromatography method development for silodosin and solifenacin in bulk and marketed formulation using analytical quality by design approach. Issue 2 (25th December 2022) - Dhiman, Shubham; Kurmi, Balak Das; Asati, Vivek
Abstract: A reliable HPLC method for the simultaneous estimation of Silodosin and Solifenacin was developed using the quality by design approach. In this study, the main goal was to find a dependable chromatographic system for acceptable component separation. The peaks were sharp within a reasonable run time. For the risk measurement related to the study, critical quality attributes were evaluated. To create an analytical design and a control strategy, the quantitative relationship between critical materials attributes and critical quality attributes was built utilizing the Box‐Behnken design. The optimum and ideal mobile phase ratio selected as per the quality by design approach was acetonitrile:methanol:buffer (50:20:30, v/v/v) which has a pH 4.5 flow rate of 1 ml/min. The buffer system used in this mobile phase was potassium dihydrogen orthophosphate. The retention time for Silodosin and Solifenacin determined was 3.626 and 5.754 min. respectively at λmax = 210 nm. The R 2 value calculated for Silodosin and Solifenacin was 0.9994 and 0.9982, respectively. The related standard deviation was less than 2% for the developed method showing good reproducibility and recovery. A simple, precise, and repeatable high‐performance liquid chromatography method for regular quality control testing was developed simultaneously by applying a quality by design approach.